2015
DOI: 10.1155/2015/572942
|View full text |Cite
|
Sign up to set email alerts
|

Microperimetric Biofeedback Training Improved Visual Acuity after Successful Macular Hole Surgery

Abstract: Purpose. To evaluate the efficacy of setting a preferred retinal locus relocation target (PRT) and performing Macular Integrity Assessment (MAIA) biofeedback training in patients showing insufficient recovery of best corrected visual acuity (BCVA) despite successful closure of an idiopathic macular hole (MH). Methods. Retrospective interventional case series. Nine eyes of 9 consecutive patients with the decimal BCVA of less than 0.6 at more than 3 months after successful MH surgery were included. A PRT was cho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 22 publications
1
26
0
Order By: Relevance
“…The PRL was chosen within central 2 degrees, and a 10 min training was repeated at least three times within three months. After training, patients demonstrated a significant increase in visual acuity, whereas fixation stability did not change significantly [31].…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…The PRL was chosen within central 2 degrees, and a 10 min training was repeated at least three times within three months. After training, patients demonstrated a significant increase in visual acuity, whereas fixation stability did not change significantly [31].…”
Section: Discussionmentioning
confidence: 84%
“…The microperimetry uses the cerebral plasticity and neurosensory adaptation capabilities to improve the visual performance [27]. Previous studies with biofeedback technique using acoustic tone demonstrated the possibility to improve visual function, reading speed, fixation behavior and retinal sensitivity in several macular pathologies, as age-related macular degeneration (AMD), macular hole, rhegmatogenous retinal detachment, and macular dystrophy [27][28][29][30][31][32][33]. Moreover, a flickering visual stimulus is useful in the rehabilitation of patients with low vision at the late stage of AMD [34].…”
Section: Introductionmentioning
confidence: 99%
“…BFT is reported to be dependent on the location, with the highest retinal sensitivity in small central scotomata [22]. However, we explored the possibility of standardized BFT in cases with any central scotoma size.…”
Section: Discussionmentioning
confidence: 99%
“…These improvements regard visual acuity, retinal sensitivity, fixation stability, as well as reading speed. (10,41,57,59,60) Tarita-Nistor et al conducted a study on PRL relocation using microperimeter MP-1. The new PRL location was chosen in the upper part of the retina in all cases, approximately located at the same radial distance from the old PRL.…”
Section: Preferred Retinal Loci (Prls)mentioning
confidence: 99%